PENGEMBANGAN MEDIA VIDEO ANIMASI MATERI SIKLUS AIR UNTUK SISWA KELAS V SDN TAMBAN BANGUN BARU 1 - Ria Mayasari; Lili Agustina; Fitria (JURUSAN PENDIDIKAN GURU SEKOLAH DASAR, 2023)
The use of inappropriate learning media can cause students to lack understanding of learning, especially IPA learning. The problem that occurs in students of class V of Tamban Bangun Baru 1 elementary school is that teachers do not utilize facilities so that students do not understand the material, one of which is water cycle material. One medium that can be used to help students understand the water cycle is animated video. The purpose of this study was to find out the validity, practicality, and validity of animated videos related to the water cycle. This research is a type of research and development (R & D) with the ADDIE model, namely 1) Analysis, 2)Design, 3)Development, 4) Implementation, 5) Evaluation. Subjects in the study are expert validators of media, materials, language, question materials, teachers and students. The trial was conducted face-to-face. The data analysis techniques used are quantitative from validation sheets, questionnaires, question tests. The results of this study are the validity of the animation video material expert by 61% (feasible). the validity of the water cycle material animation video media is 76% (valid), the validity of the animation video language is 83% (very valid) and the question material is 67% (quite valid). The practicality of animated video media by 97% (very practical) then the response of the students to the animated video is 91.6% (very interesting). Pretest student learning completion results of 62% (not completed) and posttest student learning completion results of 91.3% (completed). Thus, the animation video media on the learning of water cycle materials subthema 1,2 and 3 learning 1.2 and 5 students of class V of Tamban Bangun Baru 1 elementary school was able to improve student learning outcomes.